2021
DOI: 10.3847/2041-8213/abdcb6
|View full text |Cite
|
Sign up to set email alerts
|

Constraining Primordial Black Holes with Dwarf Galaxy Heating

Abstract: Black holes formed in the early universe, prior to the formation of stars, can exist as dark matter and also contribute to the black hole merger events observed in gravitational waves. We set a new limit on the abundance of primordial black holes (PBHs) by considering interactions of PBHs with the interstellar medium, which result in the heating of gas. We examine generic heating mechanisms, including emission from the accretion disk, dynamical friction, and disk outflows. Using the data from the Leo T dwarf g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 36 publications
0
46
1
Order By: Relevance
“…Finally, we comment on a numerical difference in the cooling rate compared to the previous works (Wadekar & Farrar 2019;Lu et al 2020). We have found a factor three larger cooling rate compared to what was found in Wadekar & Farrar (2019).…”
Section: Metallicitycontrasting
confidence: 38%
See 1 more Smart Citation
“…Finally, we comment on a numerical difference in the cooling rate compared to the previous works (Wadekar & Farrar 2019;Lu et al 2020). We have found a factor three larger cooling rate compared to what was found in Wadekar & Farrar (2019).…”
Section: Metallicitycontrasting
confidence: 38%
“…We note that Leo T as well as cold gas clouds in Milky Way have been already investigated to constrain scattering cross sections of WIMP dark matter with the standard model particles (Bhoonah et al 2018(Bhoonah et al , 2019Farrar et al 2020;Wadekar & Farrar 2019). In addition, Lu et al (2020) has recently shown that accreted disk around solar mass PBHs as well as dynamical friction could also heat interstellar gases, and that Leo T can be used to constrain PBHs for the masses above 𝑀 .…”
Section: Introductionmentioning
confidence: 99%
“…The strongest ones come from the NANOGrav experiment [92] (applicable only for PBHs formed from collapse of density perturbations and in the absence of non-Gaussianities; see Refs. [93,94]), CMB distortions (Planck D and Planck S) [55,73], x-rays (XRay) [95,96], x-ray binaries (XRayB) [97], EROS [98], Icarus [99], radio observations (Ogle) [100], and dwarf galaxy heating (DGH) [101]. Constraints on monochromatic PBH mass functions are adapted to extended mass functions with the techniques described in Refs.…”
mentioning
confidence: 99%
“…While PBHs in this mass-range are subject to a variety of constraints, they often rely on a number of assumptions. A powerful cosmology-independent approach for exploring such PBHs is analyzing their interactions, energy deposition and heating of the surrounding interstellarmedium gas [45,46]. As shown on Fig.…”
Section: Pos(eps-hep2021)148mentioning
confidence: 99%